Лучшие рассказы для детей - Астафьев Виктор Петрович (Школьное чтение, 2022)
Экземпляры: ф. 20 (20230321) / Инвентарный номер: 65330 / Цена: 186.00 / Авт.знак: А 91 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6